PENGUATAN KEPEMIMPINAN PEREMPUAN MUDA BERBASIS KADERISASI IDEOLOGIS MELALUI PELATIHAN INSTRUKTUR NASYIATUL AISYIYAH (LINA) DI PAPUA: Strengthening Young Women’s Leadership Based on Ideological Cadre Development through the Nasyiatul Aisyiyah Instructor Training (LINA) Program in Papua - Wahyu Kumala Sari; Rusniawati; Muhamad Sofian; Siti Rohmatin Fitriani; Sulasih; Mafatial Q Ulinuha; Imam Alfian kadir (LPPM Universitas Muhammadiyah Papua, 2026)
The Nasyiatul Aisyiyah (LINA) Instructor Training program in Papua was designed to strengthen young women's leadership based on ideological cadre development within the context of the Nasyiatul Aisyiyah organization, which is rooted in Muhammadiyah values. This intervention addresses the challenges of limited ideologically and pedagogically competent instructors and disparities in access to cadre development resources. The approach used was intensive training using participatory action research methods, involving dialogic lectures, focus group discussions, critical reflection, and microteaching. The training focused on Muhammadiyah and NA ideology, the cadre development system, instructional facilitation, and training ethics. The results demonstrated an increased capacity of prospective young female instructors in understanding ideology, the cadre development system, and facilitation skills. The main output was the formation of 24 prospective instructors ready to support cadre regeneration in Papua and the establishment of a strategic follow-up plan, the Nasyiatul Aisyiyah Instructor School (SINISA). This activity demonstrated the practical significance of strengthening the ideological cadre development system in eastern Indonesia.